Please wait...
Contact Us
Contact
Need assistance? Contact us on below numbers

For Study plan details

10:00 AM to 7:00 PM IST all days.

Franchisee/Partner Enquiry (South)

Franchisee/Partner Enquiry (North, West & East)

OR

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this number

9372462318 / 9987178554

Mon to Sat - 10 AM to 7 PM

PROVE: sinA/cotA+cosecA=2+ sinA/cotA-cosecA

Asked by Krithi K 6th April 2012, 9:14 PM
Answered by Expert
Answer:
LHS = 
sinA/(cotA+cosecA)
= (sinA)(cosecA-cotA)/(cosecA+cotA)(cosecA-cotA)
= (1-cosA)/(cosec2A-cot2A)
= (1-cosA)/1 = 1-cosA

RHS = 
2+(sinA)/(cotA-cosecA)
= 2+(sinA)(cotA+cosecA)/(cotA-cosecA)(cotA+cosecA)
= 2+(cosA+1)/(cot2A-cosec2A)
= 2+(cosA+1)/(-1)
= 2-cosA-1
= 1-cosA

LHS=RHS=1-cosA
Hence proved
Answered by Expert 8th April 2012, 4:04 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Free related questions

ICSE QUESTION ANSWERS

Browse free questions and answers by Chapters

Chat with us on WhatsApp